Assessing the impact of rice policy changes in Viet Nam and the contribution of policy research - Ryan, James G. (International Food Policy Research Institute, 1999)
The marketing and policy research on rice of the International Food Policy Research Institute (IFPRI) is described, and the conclusions and recommendations are discussed in the context of the decisionmaking processes in Viet Nam. The role of IFPRI's publication and communications in informing the policy environment are discussed. The author describes the perceptions of partners and stakeholders of the influence of the outcomes of the IFPRI project. They show that the research was regarded as being of high quality, independent, rigorous, and timely. A strong foundation of primary and secondary data gathering and analysis from Viet Nam gave the modeling work on policy options a high degree of credibility among key policymakers. Linking the spatial equilibrium model with income distribution analysis based on national household surveys allowed IFPRI to satisfy policymakers that relaxing rice export quotas and internal trade restrictions on rice would not adversely impact on regional disparities and food security and would have beneficial effects on farm pricesand poverty, giving a degree of confidence to policymakers that relaxing the controls would be in Viet Nam's national interest. They made these decisions earlier than would have been the case without the IFPRI research. A framework for the evaluation of policy research and advice is described, which explicitly recognizes the possibility of alternative suppliers of these two components to IFPRI. The framework is used to assess the impact of IFPRI's research with Viet Nam on alternative internal and external trade policies for rice in that country. The policy assessment framework is used to measure the economic impact of the policy changes, and the contribution of IFPRI's work with Viet Nam on the policies from 1995–97. Around 40 percent of the contribution of IFPRI is estimated to have accrued to the rest of the world as Viet Nam is now a major player in world rice trade.